TRANSFORMATION OF WOMAN AND NATURE IN ENVIRONMENTAL POLITICALIZATION: ECOFEMINISM - YILMAZ ASLANTÜRK, Arzu (SSD Journal, 2018)
The aim of this study is to examine the ecofeminism regime seeking and the location of the ecowoman between patriarchal values, which appear to be the relationship between ecology and feminism in social spheres. After the 1980s, feminist rhetoric began to turn into a green establishment, called ecofeminism, integrated with the political discourses of those who are trying to find solutions to environmental problems, protecting ecology. In addition, the classical ecological movements of environmentalism search for the source of ecological crises in humans, while the ecofeminist movement calls the source of the nature crisis to the masculine world view. The concepts of private ownership, nature, public space, culture and modernity, which are frequently used in feminist analyzes, make women a subject of social movements in the eye of ecology. This study, which advocates that feminism is on the agenda of environmental problems, is mainly based on the assumption that women’s movements are effective in politicizing the periphery. In addition, it will be attempted to show that the relationship between nature and ecofeminism is decisive in political ideologies.